LITERASI KEUANGAN - Ricky Tri Agustian; Dimas Wibisono (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This research aims to analyze the influence of financial literacy, perceived benefits, hedonic motivation, and risk perception on the decision to use the Indonesian Standard Quick Response Code (QRIS) payment method. Employing a quantitative approach, data were collected from 300 respondents who were QRIS users through an online survey (Google Form). Data analysis was conducted to examine the relationships among the variables. The results indicate that financial literacy and perceived benefits have a positive and significant impact on the decision to use QRIS. Hedonic motivation demonstrates a positive but nonsignificant influence on the decision to use QRIS, while risk perception has a negative and nonsignificant effect. The implications of these findings provide valuable insights for stakeholders in the financial industry and the government to enhance QRIS adoption by considering financial literacy, perceived benefits, hedonic motivation, and risk perception